2020
DOI: 10.1002/dmrr.3285
|View full text |Cite
|
Sign up to set email alerts
|

Complicated curve association of body weight at diagnosis with C‐peptide in children and adults with new‐onset type 1 diabetes

Abstract: Aim: To investigate the association of body mass index (BMI) or BMI z-score (BMIz) at diagnosis with β-cell function in new-onset type 1 diabetes (T1D) patients in children and adults.Methods: This was a retrospective cohort study; 256 children (<18 years) and 245 adults (≥18 years) with less than 1-year duration were recruited and followed for 4 years with an interval of 12 months. Smooth curve fitting, a two-piecewise linear model, and Cox proportional hazards models were utilized to investigate the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The association between BMI and T1DM progression is conflicting. Some studies showed that patients with higher BMI had better beta cell function at diagnosis and after follow-up (16)(17)(18). However, other studies showed that BMI might be a risk factor for developing T1DM and for accelerating T1DM progression (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…The association between BMI and T1DM progression is conflicting. Some studies showed that patients with higher BMI had better beta cell function at diagnosis and after follow-up (16)(17)(18). However, other studies showed that BMI might be a risk factor for developing T1DM and for accelerating T1DM progression (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of U.K., TrialNet, and Chinese cohorts has identified two distinct phases of C-peptide decline in stage 3 disease: an initial exponential fall followed by a period of relative stability. Along with initial differences at the time of clinical diagnosis, the rate of decline over 2-4 years was inversely related to age at onset (10,(34)(35)(36). Furthermore, the U.S. T1D Exchange Study found that glycemic control was better in adults with type 1 diabetes than in children and adolescents with type 1 diabetes (37).…”
Section: Metabolic Characteristics Of Adult-onset Type 1 Diabetesmentioning
confidence: 99%
“…12 For adults (>18 years old), BMI was converted to BMI-z score as [BMI-mean (BMI)]/SD (BMI). 13 Subjects had blood drawn for plasma glucose, glycated haemoglobin A 1c (HbA 1c ), triglycerides, total cholesterol, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C). The urine sample was also collected for a test of glycosuria and ketonuria.…”
Section: Data Collectionmentioning
confidence: 99%
“…4 However, it is important to note that the knowledge acquired from studies based on these registries cannot be directly applied to the Chinese population due to differences in the incidence of T1D, the associations of genetic background, the frequency of islet-related autoantibodies, and the distribution of clinical subtypes between East Asian and Caucasian populations. [5][6][7][8][9][10][11][12][13][14][15][16][17] Several regional studies have been conducted within China, including the Guangdong Provincial Translational Medicine of Type 1 Diabetes, 7 a single-centre retrospective hospital study in Henan, 8 and the 3C study in Beijing and Shantou. 9 These studies have reported the demographic and informatics features, clinical characteristics at onset, complications, and comorbidities of Chinese T1D patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation